THE PDCA APPROACH WITH OEE METHODS FOR INCREASING PRODUCTIVITY IN THE GARMENT INDUSTRY - Hibarkah Kurnia; Choesnul Jaqin; Humiras Hardi Purba (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2022)
The production process of the garment industry with socks products in a company often has problems with a decrease in machine productivity. Production results still cannot reach the production target and result in disruption of delivery to customers. This study aims to determine the main causes that affect the decline in production and provide solutions to increase production. The method used in this research is the Plan-Do-Check-Action (PDCA) approach and the Overall Equipment Effectiveness (OEE) method. This method is appropriate in analyzing increased production and measuring the effectiveness of the use of equipment in production efficiency. The results of this study can determine the main causes that affect production decline using Failure Models and Effects Analysis (FMEA), namely, the standard speed fluctuates 336 RPN, medium speed 245 RPN, sloping creel 150 RPN, narrow engine room 120 RPN, and dirty engine 72 RPN. The measurement of the effectiveness of the use of equipment in terms of production efficiency (OEE) before the repair is 63% and after modification is 73%, meaning that the OEE value after the change has increased by 8%. This is evidenced by an increase in production output by 112% on an average per machine/month.